Organization of NMDA receptors at extrasynaptic locations - Petralia, Ronald S. (2010)
NMDA receptors are found in neurons both at synapses and in extrasynaptic locations. Extrasynaptic locations are poorly characterized. Here we used preembedding immunoperoxidase and postembedding immunogold electron microscopy and fluorescence light microscopy to characterize extrasynaptic NMDA receptor locations in dissociated hippocampal neurons in vitro and in the adult and postnatal hippocampus in vivo. We found that extrasynaptic NMDA receptors on neurons in vivo and in vitro were usually concentrated at points of contact with adjacent processes, which were mainly axons, axon terminals, or glia. Many of these contacts were shown to contain adhesion factors such as cadherin and catenin. We also found associations of extrasynaptic NMDA receptors with the MAGUKs, PSD-95 and SAP102. Developmental differences were also observed. At postnatal day 2 in vivo, extrasynaptic NMDA receptors could often be found at sites with distinct densities whereas dense material was seen only rarely at sites of extrasynaptic NMDA receptors in the adult hippocampus in vivo. This difference probably indicates that many sites of extrasynaptic NMDA receptors in early postnatal ages represent synapse formation or possibly sites for synapse elimination. At all ages, as suggested in both in vivo and in vitro studies, extrasynaptic NMDA receptors on dendrites or the sides of spines may form complexes with other proteins, in many cases, at stable associations with adjacent cell processes. These associations may facilitate unique functions for extrasynaptic NMDA receptors.